Sociohistorical Analysis of Normative Standards of Masculinity in the Pandemic of COVID-19: Impacts on Men’s Health/Mental Health - de Sousa, Anderson Reis; Moreira, Wanderson Carneiro; da Silva Santana, Thiago; Araújo, Isabella Félix Meira; Borges, Cléa Conceição Leal; Almeida, Éric Santos; das Mercês, Magno Conceição; da Silva, Richardson Augusto Rosendo; Teixeira, Jules Ramon Brito; Lourenção, Luciano Garcia; Gomes, Nadirlene Pereira; de Santana Carvalho, Evanilda Souza; et al. (Frontiers in Psychology, 2022)
Objective: Analyzing sociohistorically how the normative patterns of hegemonic masculinity generate deleterious impacts on men’s health in the context of the COVID-19 pandemic. Methods: A qualitative study from a socio-historical perspective conducted with 50 men, based on an online survey. A semi-structured form was applied. The data were analyzed by the Collective Subject Discourse method, interpreted in the light of the context of epidemic disease and hegemonic masculinity. Results: The experience of the pandemic exposed the normative patterns of masculinities from the consummation of acts representative of the pandemic context, which incited men to deny the existence of COVID-19 disease, as well as to delay the understanding and adoption of measures to protect and control COVID-19. As repercussion, men presented conflicts in the regulation of emotions, emotional suppression, were more reactive, felt threatened regarding the loss of the role of family provider, virility, and revealed a sense of invulnerability, added to the weakening of self-care. Conclusion: The male discourse revealed that men have their masculinity structured in the hegemonic model, but express signs of recognition that this model causes harm to themselves and their health.